Prostaglandin Analogues Versus Topical Beta-Blockers in the Initial Pharmacological Management of Primary Open-Angle Glaucoma: Clinical Effectiveness and the Role of Medication Adherence - Naufal Prama Putra; Ghani Phalosa; Andi Muhammad Fajri Rusdianto (Indonesian Journal of Innovation Multidisipliner Research, 2026)
Primary open-angle glaucoma is a progressive optic neuropathy requiring sustained intraocular pressure control to prevent irreversible visual loss. Prostaglandin analogues and topical beta-blockers are widely used pharmacological therapies, although their clinical effectiveness is influenced by efficacy, safety, dosing convenience, and patient adherence. This narrative review compared the clinical effectiveness of both drug classes and examined the role of adherence in long-term treatment outcomes. Literature published primarily between 2021 and 2026 was identified from PubMed, Scopus, Web of Science, ScienceDirect, and Google Scholar. Prostaglandin analogues generally provide greater and more sustained intraocular pressure reduction than topical beta-blockers, with once-daily administration offering an additional practical advantage. However, local ocular and periocular adverse effects may reduce treatment acceptance. Topical beta-blockers remain effective alternatives for selected patients, although cardiovascular and respiratory adverse effects require careful consideration. The clinical benefits of both therapies may be reduced by missed doses, incorrect eye-drop administration, adverse effects, treatment cost, and limited medication access. Therefore, prostaglandin analogues are generally preferred as initial pharmacological therapy, whereas topical beta-blockers remain appropriate for selected patients based on tolerability, comorbidities, accessibility, and the likelihood of sustained adherence.